Unbalanced social–ecological acceleration led to state formation failure in early medieval Poland - Adam Izdebski; Sambor Czerwiński; Marek Jankowiak; Marcin Danielewski; Sabina Fiołna; Raphael Gromig; Piotr Guzowski; Negar Haghipour; Irka Hajdas; Piotr Kołaczek; Mariusz Lamentowicz; Katarzyna Marcisz; et al. (Proceedings of the National Academy of Sciences, 2025)
Rapid social–ecological intensification is a recurrent feature of human history. It occurred in different forms and contexts; its outcomes may have been sustainable or transient. Until recently, such intensifications usually accompanied state formation: Consolidation of political power was often coupled with exponential increase in human exploitation of the environment of a given area. Here, we study one such case, uniquely well-documented through our rich paleoecological, archaeological, numismatic, and literary data. Triggered by the Eurasian slave trade, the first “Polish” polity was founded in Central Europe c. 900 common era. It undertook unprecedented ecological intensification in its core territory, connected with large construction projects, and engaged in rapid territorial expansion. We provide new crucial evidence on this process by publishing here a high-resolution pollen profile from a location close to the polity’s capital and by an application of social network analysis to numismatic data. This state collapsed within a few generations after its foundation. The collapse of the political elites, however, did not produce a complete social and ecological disintegration of the polity’s former core region. We thus show how collapse and continuity can remain closely intertwined. Last but not least, the rich evidence on the mechanism of the collapse reveals that successful maintenance of social–ecological intensification requires reliance on a number of cultural, economic, religious, and social networks underlying the political expansion. The polity’s elite lacked access to or failed to mobilize such networks, which led to its demise.